PARTAI POLITIK DAN POLITIK PENCITRAAN MELALUI PEMANFAATAN MEDIA MASSA PADA PEMILIHAN PRESIDEN 2009 - Utami, Budi (Jurnal Insani, 2016)
Since direct presidential election in 2004, the politics of image among Indonesian political elites has become a common phenomenon. Susilo Bambang Yudhoyono (SBY) victory in the event was considered a success to build political imagery. Realizing that campaign activities to gain an elegant political image cannot be done overnight, a lot of political figures who have expressed their interest to run for the next presidency, in this study it is shortened as a presidential candidate -- have long embarked on various efforts for such intended purposes. Such efforts include regular visits to voters in the regional level, get involved in the social and economics activities of the people, visiting riot-torn cities and hardest-hit districts devastated by natural disaster and even helping a hand to the victims. And to some points, they appear in some ``disguised`` campaign activities in social commercials in the print and electronic media. The politics of image is done with or without any design early on. The media, as one of the communication tools to maximize the impact of the messages to be delivered, are believed to have its relevance in regard to the politics of image in the presidential candidacy. Given its geographical and demographical structures, media plays an important role in creating the political image that a presidential candidate wants to have, to reach as many potential votes as possible and in turn eventually persuade them to vote the desired presidential candidate.This research is aimed at comparing the politics of image of Megawati Soekarnoputri who is supported by the one of the country’s biggest political party and that of the politics of image of Wiranto using his new political vehicle, the Conscience Party, as his new political machine to enter Indonesia’s political system. At that time they are a potential candidate to face SBY. The research employs qualitative approach/methods, data research and analyses during the research period (2008), and divide the research areas into several indicators and then using the method of difference to find the difference between the two presidential candidates in the politics of image. Besides that, the research is also based on common political literatures. The media, interviews with the inner circles of both Megawati Soekarnoputri and Wiranto are conducated to have `inside thoughts` of the presidential candidates. Interviews with political and communication specialists, a political commentator and analyst are also conducted. And the last but not the least is the results of the surveys of the presidential candidates by the Indonesia conducted by some survey and rating companies in Indonesia.